Perbedaan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran TGT (Team Games Tournament) Berbantuan Media Smart Rocket Small - Ita Desi Saputri; Hesti Yunitiara Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model assisted by Smart Rocket Small media on students' critical thinking skills. The research method used is a quantitative approach with a Non-Equivalent Control Group Design. The population in this study consisted of all students at MI Sabilul Huda. The research sample included class VA as the experimental group and class VB as the control group. Data collection techniques involved tests through pretest and posttest, as well as non-test techniques such as observation questionnaires and documentation. Data analysis was conducted using normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference in the use of the Team Games Tournament (TGT) model with Smart Rocket Small media on students' critical thinking skills. This is indicated by a significance value of 0.000 < 0.05 in the Independent Sample T-Test, demonstrating different learning outcomes between the experimental and control groups. The average score of the experimental class was 70.6286, which was considerably higher than that of the control class at 63.9714. Based on the findings, it can be concluded that the use of the Team Games Tournament (TGT) learning model with Smart Rocket Small media can improve students' critical thinking skills.